2019
DOI: 10.1111/eci.13060
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference and abdominal volume index are the strongest anthropometric discriminators of metabolic syndrome in Spanish adolescents

Abstract: Background Waist circumference has been suggested as predictor for metabolic syndrome (MetS) in adolescents but it has not been compared with newly proposed anthropometric indexes. This study aimed to disclose the capacity of ten classic and novel anthropometric indexes to discriminate by the presence of MetS in this young population. Materials and methods A cross‐sectional study was performed on 981 adolescents (13.2 ± 1.2 years) randomly recruited from eighteen schools in south‐east Spain. Body fat percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 49 publications
7
40
1
2
Order By: Relevance
“…Therefore, AVI demonstrated excellent predictive power for IGT and DM by fully evaluating VAT (21). Previous study found that the predictive ability of AVI for MetS was better than other new anthropometric indicators and traditional indicators (35,36), and was the strongest predictor [1], which was similar to the results of this study. In this study, AVI's ability to identify MetS in non-overweight/obese people was lower than that in Spanish adolescents (AUC: 0.831 for males, 0.867 for females) (35), but higher than that in northern Iran (AUC: 0.72 for males, 0.73 for females).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, AVI demonstrated excellent predictive power for IGT and DM by fully evaluating VAT (21). Previous study found that the predictive ability of AVI for MetS was better than other new anthropometric indicators and traditional indicators (35,36), and was the strongest predictor [1], which was similar to the results of this study. In this study, AVI's ability to identify MetS in non-overweight/obese people was lower than that in Spanish adolescents (AUC: 0.831 for males, 0.867 for females) (35), but higher than that in northern Iran (AUC: 0.72 for males, 0.73 for females).…”
Section: Discussionsupporting
confidence: 89%
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
“…BRI is a predictor of body fat percentage and visceral adiposity tissue, and its values range from 1 to 16 35 . Although studies have compared the prediction of MetS by BRI with traditional and novel anthropometric indices, 41–55 there is currently no meta‐analysis indicating whether BRI is a better predictor of MetS than BMI, WC, WHR, WHtR, ABSI or BAI. Therefore, this meta‐analysis aims to investigate whether BRI is superior to BMI WC, WHR, WHtR, ABSI or BAI in predicting MetS.…”
Section: Introductionmentioning
confidence: 99%
“…The AUCs for the superlative adiposity indicators of bodyfat- and lipid-enhanced groups were both significantly higher than that for the body-shape-enhanced group ( Figure 3 ). Brazilian, Chilean, and Spanish investigators have recommended the bodyfat-enhanced indicators WHtR, AVI, and BMI as an excellent screening tool for adolescent MetS [ 39 , 40 , 41 , 42 ]. Although no adolescent studies have investigated LAP and VAI, one adult study reported that LAP was the most accurate indicator for determining male and female MetS [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have evaluated anthropometric indicators for the identification of adolescent MetS in the community have found that AVI and WC for both girls and boys in Spain, BMI/WC for females and WHtR/WC for males in Chile, and WHtR for both sexes in Brazil have an excellent capacity for discriminating MetS [ 39 , 40 , 41 ]. However, there was a lack of validation of screening accuracy and efficiency for the indicators in these studies.…”
Section: Discussionmentioning
confidence: 99%